Kitāb al-Naḥw al-Wāḍih wa al-Ṭarīqah al-Istinbāṭiyyah wa Fa’āliyyah Istikhdāmihā li Tarqiyyah Fahm al-Ṭalabah fī Qawā’id al-Naḥw - Muharidinsyah Muharidinsyah (Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia., 2020)
Textbook is important for student as main media in learning Arabic and significant to teacher for teaching besides suitable method in order to achieve necessary result, is the textbooks, however, must be fit students’ level of capability and nahwu al-wadhih is one of effective textbooks for any students’ level since it offers practical study which goes along with istinbathiyah method. Thus the writer is interested in conduct research that concerns on application of nahwu al-wadhihin Darul Hikmah boarding school, and decided to entitle this research as “effectiveness in using nahwu al-wadhih and istinbathiyah method to improve students’ understanding in Arabic grammar”. The aim of this study is to reveal the effectiveness of using nahwu al-wadhih and istinbathiyah method in Darul Hikmah boarding school and to disclose students’ responses toward Arabic grammar using nahwu al-wadhih and istinbathiyah method in DarulHikmah boarding school. This research uses a quasi-experimental design method. Research instruments for this research are interview along with pre-test and post-test. Result of study indicates that using nahwu al-wadhih and istinbathiyah method is effective to improve students’ understanding in learning Arabic grammar in DarulHikmah and students’ responses in learning Arabic grammar using nahwu al-wadhih and istinbathiyah method in Darul Hikmah are enthusiastic and excited.